FEMALE REPRESENTATIVE AND RESISTANCE IN OKA RUSMINI’S EARTH DANCE (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
FEMALE REPRESENTATIVE AND RESISTANCE IN OKA RUSMINI’S EARTH DANCE Mita Hati Priyantini English Literature, Faculty of Language and Arts, Surabaya State University. Mitahati@rocketmail.com Mamik Triwedawati SS. M.Pd. English Department, Faculty of Language and Arts, Surabaya State University Abstrak Novel Earth Dance merupakan novel karya Oka Rusmini yang menyuarakan kaum subordinasi seperti wanita maupun queer. Dalam tesis ini, penelitian di lakukan terhadap dua tokoh representatif yakni Telaga sebagai tokoh utama dalam novel dan Kenten sebagai karakter queer. Dengan demikian, dapat di rumuskan tiga masalah yaitu (1) Bagaimana penggambaran representatif wanita dalam novel Earth Dance oleh Oka Rusmini; (2) Bagaimana representatif memimpin perlawanan dalam novel Earth Dance oleh Oka Rusmini; dan (3) Bagaimana dampak dari perlawanan terhadap tokoh-tokoh dalam novel Earth Dance oleh Oka Rusmini. Data dari tesis ini di ambil dari novel sebagai sumber utama dan membaca intensif untuk langkah berikutnya. Untuk menjawab semua masalah, penelitian menggunakan teori Feminisme untuk menggambarkan representatif dan perlawanan perempuan, baik penyebab dan dampakanya. Penelitian kepustakaan di gunakan sebagai data pendukung dalam analisis. Selanjutnya, deskripsi analisis di gunakan untuk menjelaskan hasil analisis. Setelah merumuskan tiga masalah dan langkah penelitian di atas, di temukan bahwa representatif wanita yang melakukan perlawanan di sebabkan karena adanya dominasi laki-laki yang meminggirkan wanita dalam konteks budaya Bali. Namun, pada akhirnya perlawanan wanita tetap mendapatkan hukuman dari para dewa yang harus di terima. Kata Kunci: wanita, representatif dan perlawanan. Abstract Earth Dance is novel by Oka Rusmini which championing the subordinate group such as woman or queer. In this thesis, the study is focused on two representative characters; they are Telaga as the main character and Kenten as a queer character in the novel. Thus, there are three problems which will describe in this study (1) how is female representative depicted in Oka Rusmini’s Earth Dance; (2) how is female representative leads to female resistance in Oka Rusmini’s Earth dance; and (3) how is the impact of female resistance in Oka Rusmini’s Earth Dance characters. The data from this thesis are taken from novel as the main source and intensive reading for the next step. To answer the three problems, the research use theory of Feminism to depict female representative and resistance, whether the cause and impact to the doer. Library research is used as supporting data in analysis. Next is the analysis description used to explain the result of analysis. after the discussion the three problems above, the result is, that female representative did the resistance is because the male domination which subordinate them in the context of Balinese custom. Yet, in the end, these female resistance have to willingly accept their punishment from the gods. Key words : woman, representative and resistance. INTODUCTION The term of women derives from rakta swanita which means women’s seed. Balinese custom were originates from Hinduism, in which the concept of Balinese women is contiguous as Hindu women; they are born, lived and are bound with their desa adat. The concept of of unity between men and women is called arddanisvarimurthi in which men and women are described to complete each other. While Balinese custom establish the joint responsibility of a marriage couple for sociopolitical and religious duties, the earlier ethnography of Bali has often associated men as the heads of the households with the role of representing households (Nakatani, 1997:727). Nakatani found that Balinese women have not only double but also triple roles. This research is done on women’s roles in her family as a wife and mother, their social roles and a breadwinner in the custom. At the end, she calls Balinese women as wonder women. If super women are demanded to do their house chores as well as their career, ‘wonder women’ are demanded to do their role in desa adat as one of the characteristic of Balinese women. Bali which is known as the patriarchal system which oppressed women to will under men’s dominance. Balinese custom arranged women to submissive to their husband though the women is in a high caste or lower caste status without a protest (Chaitanya, 2010:4-5). For Balinese women, the primary tasks are to produce a good quality children, fostering balance and harmony within family and to work as a family team in society/adat (Suyadnya, 2006:6). In the previous age, Balinese women are work in the house and made songket to earn more money and fulfill the household needs. Married women in Balinese have also roles in maintaining the ritual represented their household. They must take care of preparation and presentation of offering, ceremonial gift-giving and ritual assistance as their main task or they divide the certain task, especially the presentation of offering and gift-giving to their daughter or another female member in the house (Nakatani, 1997:736-737). Through Nakatani’s definition of women, that the society prejudice women’s main chores are to maintaining the household and take care of their family and it has become obstacles for their career. Most of Oka rusmini’s works break taboo to tradition and vividly talking about body and erotic caused much controversy among her family, friends and even society who read her works. They might be disturbed, but she ignored. As an author, she can do something expressing her dissatisfaction, unhappiness and anxiety via the written words. Oka had produced three novel, collection of short stories and poetry, those are, Tarian Bumi (Earth Dance translated into English by Lontar foundation and German as Erdentanz), Putu Menolong Tuhan (Putu Helps His God, translated in English by Vern Cork), Sagra, Pemahat Abad (The Sculptor of the Century, translated in English by Pamela Allen), Tempurung, and Pattiwangi. In every her novels, poetry, and short stories, Oka Rusmini works are ingenious in the sense that focus almost solely on female characters and convey feminine perspective in a consistent and provocative manner. In addition to critiquing the caste system, which in her view is very much shaped and controlled by patriarchal system in Balinese Hindu, Oka depicts competition and tension among her main female characters, and this competition can often be fierce, sometimes even be violent. She explores without reservation the positive as well as the negative qualities of Balinese women from both social groups., but at the same time she never forget to reiterate that patriarchy bears the ultimate responsibility for the social problem related to the caste system. Based on background of the study above, it can be simplify the three problems which emerge as the discussion in this study. How is the female representative depicted in Oka Rusmini’s Earth Dance? How does female representative leads to female resistance in Oka Rusmini’s Earth Dance? How is the impact of female resistance in Oka Rusmini’s Earth Dance characters? In analyzing the data, this study use the theory of feminism. The theory of female resistance contains the definition of female representative which leads to resistance and the impact to the main character in the novel. RESEARCH METHOD In carrying out the study, the library reasearch, which used for literary work deal with this study, is basically descriptive and qualitative research. Most of the data collected from many speech dialogue in Oka Rusmini’s Earth Dance as the object analysis which define into twenty chapter in the novel. Earth Dance was firstly published by Indonesia Tera, Magelang, Indonesia in 2000 and was originally serialized in the newspaper Republika, 4 march-8 April 1997. The data is analyzed by using feminism criticism, which is why the librarian research is used as the method. Conducting this analysis will be used to answer the questions in the statement of the problems. The procedure of analysis divided as follows; (1) The first step is to collect data speeches, thoughts, and quotations which have relation to the discussion, (2) Then clasify the data of speeches, thought and quotations to the Telaga and Kenten as the object of analysis, (3) Selecting quotations of the data are finally analyzed by the theories that are mentioned above to describe the concept of female resistance, (4) The ideal characteristic of female resistance begins with the description of female in this novel in order to know what is the impact on Telaga’s character as the main character through other characters, (5) Finally, to depict the characterization of Telaga and the impact of female resistance to indicate the significance of resistance in Telaga’s personality, the analysis is done by the theories that have been mentioned in preeceding explanation. ANALYSIS The first question will be revealed the main problem that focuse on how female representative in Oka Rusmini’s Earth Dance. In this discussion, the female representative divide into three sub-chapters; (1) Physical description of Ida Ayu Telaga Pidada as a brahmana, (2) physical description of Kenten as a lesbian character, and (3) diferentiate of language uses between brahmana and sudra. The second question will be revealed the second problem which focuse on how is female resistance in Oka Rusmini’s Earth Dance. The discussion is emerge the main character rebells her own fate as a brahmana and female queer character who ignores the society which determine her as queer. The last question is, how is the impact of female resistance to the main character will be revealed by the discussion which divide into four sub-chapters; (1) punishment for rebel the caste system, (2) Telaga exilled from griya, (3) Telaga changing caste, and (4) Kenten isolated from society. Oka Rusmini’s Earth Dance brings up the issues of gender and class-society. Narrated by Ida Ayu Telaga surrounded by four women who shapes Telaga’s character and resist from her own custom, which in Telaga’s mind was unfair. Telaga is a brahmana woman who feels trapped and unhappy with her own caste and custom. Her mother was a sudra who ambitious to married only to brahmana man. One the issue which cause problematic among woman is physical appearance. It is like that they were race as the most beautiful among others. Physical appearance of main character in Oka Rusmini’s Earth Dance Telaga is describe as beauty as a goddess and belongs to brahmana. Made the other girls envy of her. When she was danced oleg, it had always been a public secret that nobody could surpass Ida Ayu Telaga Pidada. Oleg is a dance of love, a dance about delights of romance, about the beauty of courtship (Earth Dance, 2011:13). One of the prominently character named Kenten. She is a best friend of Sekar and also the female queer character. She is a commoner and living only with her mother. Her father was disappeared and doesn’t mention in the novel. she was a woman with ten men power and well built phsically strong. Kenten realizes since the begining of her different in desire. Although, she has to play the role of woman, especially in every month when a blood flows between her two legs. She needs to cleanse her body every month. Language system to caste is describes in Oka Rusmini’s Earth Dance in some of dialogues and monologue of Telaga’s, as in evident in Telaga’s speak as third-person narratives below: “Telaga considered him as an idiot, but an idiot who she had to approach with respectful titles: aji – noble father, or ratu – lord. He was a man without character; a man who could be proud of nothing but his masculinity. How could she trust him? As a child, Ida Ayu Telaga Pidada had ashamed to call him her respected father. Telaga’s father had an Ida Bagus as a father and Ida Ayu as a mother, so people said his noble blood was of the very highest carat. And so, Telaga had to call this man she hardly knew “Ratu”.” (P.17) Through the quotation above is proving that Language uses was strictly adhered by Balinese people. In the past infringement of these rules were harshly punished by fines and even debt slavery. Today, the extreme of language use have been largely abandoned because these sanction can no longer be applied. In Balinese caste system, everything has arranged even in the language uses. The Balinese language is itself a hierarchical, while most words have only one form and is thus insensitie to status; some 1,500 everyday words have two or more lexemes which are hierachically ranked and thus status highly sensitive. The basic rule is that the inferior must uses refined when speaking to a superior caste, whereas superior may use less refined to inferior caste (Howe, 2005:113). In Oka Rusmini’s Earth Dance brings up the issues of gender and class-society. Narrated by Ida Ayu Telaga surrounded by four women who shapes Telaga’s character and resist from her own custom, which in Telaga’s mind was unfair. Telaga is a brahmana woman who feels trapped and unhappy with her own caste and custom. Her mother was a sudra who ambitious to married only to brahmana man. Throughout her entire childhood, Telaga witnesses the oppresive forces of adat and their impact on her mother, wondering if this is what it means to be a noble woman. She can only oppose the practice silently, asking herself many questions while watching the harsh life that her mother has to endure as an ex-sudra woman who has dared to enter the sacred brahmana realm. Telaga’s own daily life is mostly confined by the griya walls and the complex rules that regulate her almost every move. Telaga’s state of mind with regard to all these restriction is conveyed by free indirect speech. “Unfortunately, she could not enjoy that time for long. Telaga inevitably had to return this borrowed era to Life. She wished she could trick her way back into childhood, even just for a day or two. If only she could, she would grab that time and hide it so Life couldn’t find it and ask Telaga for its return. But Telaga could not persuade all-powerful Life to compromise. Life insisted on the following of rigid rules: rules that could not be bent, even slightly.” (P.57) The quotation blur’s the narrator voice and what occur’s in Telaga’s mind. The narrator is involved emotionally in Telaga’s lament concerning her lost childhood because of her noble status. Telaga is actually complaining about the gods’ cruel decision to snatch her childhood so quickly from her, but such complain can only be uttered in the form of a monologue. And moreover, it is softened to the point that it sounds more like nagging than protesting, as if Telaga wants to be sure that it will not offend the gods. Differ from Telaga, Kenten is sudra and the queer character who has different desire for mostly normal women. in Oka Rusmini’s Earth Dance who describe as a stubborn woman. No one dared to bother her. Like Luh Sekar, she disdains men, but whereas Luh Sekar is willing to use men to achieve her ambitions, Luh Kenten does not need men and never intends to marry one for any reason. The novel describes her as a lesbian. She feels sexually aroused by looking at Sekar’s naked body, but develops an aversion towards her own feminine body. As the result of resistance, female representative in the novel are willingly to receive the consequences of their desire against the rules. The main characters in the novel; Telaga and queer character; Kenten, are the most impacted because of their desire to resistance from the persistent custom which subordinate them. The consequences which had to be submissive by Telaga and Kenten will impact on their entire life. Delueze explain that power do not repression of desire, instead it is the expansion of desire (Colebrook, 2002:91). Ideology is take the concepts of how individual acts against their interest. Colebrook framed that feminity seen in the Jane Austen’s or any novelistic composition of character describes on the fabrics, skin colour, gestures, rhythms of speech and body parts – the thiness of waist which it is become the misspresented of ideological stereotypes of woman. Woman is a group of socialy coded affect and intensities that have gone into making up the image of personhood (Colebrook, 2002:93). It is the law of Balinese hinduism if a noble woman who marry man bellow their caste will be exilled from her house. She no longger posses nobility and she cann’t posses everything from her former house. Her child will be her husband caste (Avelling, 2006:2). Telaga and Wayan couldn’t bear the feelings any longer even they tried harder to ignore it. So, they decide to face every risk which confronts them. Begin with Telaga who exilled from griya and do not allowed to bring anything from her former house. She her child must join to Wayan’s caste as a sudra and living with her mother-in-law who opposes her marry to her only son. Yet, because Telaga is no longer a brahmana, she must address everyone in griya with the highest title – Ratu. The worst of it, Wayan found dead in his studio. Telaga had to endure Wayan’s mother and sister who since begining didn’t accept she coming to their house. Luh Gumbreg who realize that Telaga didn’t get blessing from her family before she married with Wayan, ask Telaga to held pattiwangi ritual. The ritual which is remove the noble status from noble woman who marry a commoner. The ritual is also become the reminder for the others noble women to not do the same thing as Telaga. CONCLUSION Oka Rusmini is a Balinese writer who assert Balinese tradition in every her novel. Earth Dance is one of her novel which brings up the issue of female representative who resist against subordination. The main character, Ida Ayu Telaga as the narrator, represent female in high class-caste society who against the people grouping in Hinduism. Divide people into four categories and determine them based those categories. The higher the class-caste, the more they receive privilages and subordinate the lowest caste. While, the queer character – Kenten as a commoner must facing society’s judge because her queerness. Both Telaga and Kenten who are representative their female in Balinese society and resist with their own ways. Telaga choose to betray her caste by marrying a commoner – Wayan Sasmita, and receive insult whether from people in griya even her own mother and from Wayan’s family. She is no longer a noble woman, instead she is a commoner such her husband. Her child also bear the caste of her husband as a commoner. Through Telaga’s action, she unintentionally purify her mother’s past mistake by marry a brahmana man. Kenanga who was a pragina is a sudra who ambitious marry only to a brahmana man, after she finally marry Ida Bagus Tugur – Telaga’s father, she never living a peace. Ida Bagus Tugur was marry Kenanga only to posses Kenanga’s body. Differ from Telaga, Kenten as a female queer resist from her society by ignoring people’s jugdements. Kenten is Kenanga’s close friend. They become closer because of people in the village consider them as a shame. Since Kenanga was kid, her father caught for joining the Communist party, and since then people judge her as a communist’s daughter. Kenten who desire for Kenanga’s body could only keeping a secret for herself. No one she could confide in, although everybody in the village knews her intimacy with Kenanga. It can be conclude that female representative in Oka Rusmini’s Earth Dance resist from rules that subordinate them. The rules which determine them to be truely woman who submissive to their husband and family. A woman who strong and balance the household. As the consequences of their resistance, they should abandon and willingly receive what destiny determine them according to the Balinese Hinduism law. REFERENCES Andrini, Susi. 2003. “Oka Rusmini’s Pen Breaks Tradition”. Dalam The Jakarta Post, 24 Januari. Jakarta. Blair, Emily. 2007. Virginia Woolf And The Ninetenth-Century Domestic Novel. New York: New York Press. Colebrook, Claire. 2002. Routledge Critical Thinker: Gilles Delueze. London: Routledge Darma Putra, I Nyoman. 2011. A Literary Mirror: Balinese reflections on modernity and identity in the twentieth century. Nethrlands: KITVL Press. Howe, Leo. 2005. The Canging World of Bali Religion Society and Tourism. Abingdon: Routledge. Morton, Stephen. 2003. Routledge Critical Thinker: Gayatri Cakravorty Spivak. London: Routledge. Homer, Sean. 2005. Routledge Critical Thinker: Jacques Lacan. Abingdon: Routledge McAfee, Noëlle. 2004. Routledge Critical Thinker: Julia Kristeva. London: Routledge Salih, Sara. 2002. Routledge Critical Thinker: Judith Butler. London: Routledge. Thornham, Sue. 2000. Feminist Theory and Cultural Studies: Stories of Unsetted Relation. Terjemahan Asma Bey Mahyudin. Yogyakarta: Jalasutra. Internet Source: Nakatani, A. 1997. Private or Public?: Defining Female Roles in The Balinese Ritual Domain. Southeast Asian Studies, (Online), Vol 34, Nomor 4, (http://repository.kulib.kyotou.ac.jp/dspace/bitstream/2433/56616/1/KJ00000131966.pdf?origin=publication_detail diakses 12 Februari 2014). Wayan Suyadnya, I. 2006. Balinese Women and Identities: Are They Trapped In Tradition, Globalization Or Both?, (Online), (http://qjournal.co.id/new/index.php/paper/1598/balinese-women-and-identities-are-they-trapped-in-traditions-globalization-or-both-, Diakses 12 Februari 2014). Bell, Millicent. 1986. Female Regional Writing: An American Tradition. Revue française d'études américaines, (Online), No. 30, (http://www.jstor.org/stable/20873460, diakses 26 Januari 2014). Zatlin, Phyllis, 1987. Women Novelists in Democratic Spain: Freedom to Express the Female Perspective. Anales de la literatura española contemporánea, (online), Vol. 12, No. 1/2, (http://www.jstor.org/stable/27741803, diakses 26 Januari 2014). Rodgers, Audrey T. 1979. Images of Women: A Female Perspective. College Literature, (online), Vol.6, Nomor 1, (http://www.jstor.org/stable/25111245, diakses 26 Januari 2014). Peacock, Martha M. 1993-94. Geertruydt Roghman and the Female Perspective in 17th-Century Dutch Genre Imagery. Woman’s Art Journal, (online), Vol. 14, Nomor 2. (http://www.jstor.org/stable/1358443, diakses 26 Januari 2014). Niehof, A. 1998. The changing lives of Indonesian women; Contained emancipation under pressure, (online), (http://www.kitlv-journals.nl, diakses 12 Februari 2014).